2015
DOI: 10.1007/s00268-015-3327-7
|View full text |Cite
|
Sign up to set email alerts
|

Partial Thyroidectomy for Papillary Thyroid Microcarcinoma: Is Completion Total Thyroidectomy Indicated?

Abstract: Thyroid lobectomy is an effective surgical strategy to manage papillary microcarcinomas with low complications. Routine completion thyroidectomy is not mandatory. Appropriate selection excluding high-risk patients is of paramount importance in order to achieve the best results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 60 publications
2
35
0
Order By: Relevance
“…Physicians consider differentiated thyroid cancer an indolent disease that will have a good outcome if correctly treated at diagnoses. As a result, there is a global tendency to treat DTC less aggressively over the years (8)(9)(10)(11)(12). However, since its extremely low mortality is balanced by its high prevalence, the number of deaths cannot be overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…Physicians consider differentiated thyroid cancer an indolent disease that will have a good outcome if correctly treated at diagnoses. As a result, there is a global tendency to treat DTC less aggressively over the years (8)(9)(10)(11)(12). However, since its extremely low mortality is balanced by its high prevalence, the number of deaths cannot be overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Donatini et al 24 reported a series of 880 patients over a 24 years period which included patients with papillary thyroid microcarcinomas. In the group who underwent total thyroidectomy, there were no loco-regional or distant recurrences but complication rate, both temporary and permanent, were higher.…”
Section: Primary Thyroid Surgerymentioning
confidence: 99%
“…Thyroid cancer is the most common endocrine malignancy, with 62980 estimated new cases in the United States in 2014 [1].…”
Section: Introductionmentioning
confidence: 99%
“…Papillary thyroid carcinoma (PTC) accounts for about 80% to 90% of all thyroid cancers [1] [2]. The long-term prognosis is usually excellent with a 10-year survival rate of up to 98% [1] [3] [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation